CULTURAL LITERACY DEVELOPMENT BASED ON LOCAL ORALSTORIES AS THE CULTURAL IDENTITY OF KEBONSARI ELEMENTARY SCHOOL - Tristan Rokhmawan; M. Bayu Firmansyah (Jurusan Sastra Indonesia, 2017)
In this research the researcher collects philology materials, local oral stories, forms stories in a story book and uses them as a basis for developing a literacy program based on local oral stories entitled Sekolah Berbudaya Lisan (SBL). By adopting ethnographic and philological methods the researchers collect local oral story data around the school to be transformed into a written form of children's stories in picture books. This storybook based on local oral stories becomes the foundation of the embodiment in developing and cultivating a literacy activity program which is done by combining 4D research and social engineering research methods. The SBL program was developed to create role models for social engineering activities for schools to develop the cultural behavior of oral literacy in their environment. SBL as well as making local oral stories as a distinctive characteristic that must be preserved. Schools become cultural centers of oral stories and preserved forms of local oral stories that are almost extinct because modern society has abandoned traditional oral storytelling.